Фізична географія України - Нетробчук, Ірина Марківна; Полянський, Сергій Володимирович; Netrobchuk, Iryna M.; Polianskyi, Serhii V. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Практикум містить завдання лабораторних робіт із курсу «Фізична географія України». Завдання лабораторних робіт уключають статистичний матеріал, картографічні заготовки, методичні поради щодо їх виконання. Видання рекомендоване студентам напряму підготовки 6.040104 «Географія» освітньо-кваліфікаційного рівня «Бакалавр» денної та заочної форм навчання вищих навчальних закладів і викладачам географічних спеціальностей, оскільки містить не лише розробки лабораторних робіт, але й значну кількість цікавого й корисного матеріалу про фізико-географічні особливості України.

The edition is formed of tusks for laboratory works from main themes of the course. They are: geological and morphological structure, mineral resources, the climate condition and resources, internal water and water resources, soil and vegetation cover, flora and fauna, landscapes and physico-geographical regionalization. The tusks from laboratory works consisted of statistic and cartography material, methodological advice on their execution. It is recommended for students obtaining a bachelor qualification in the study of “Geography” in any full-time or correspondence forms of study in higher educational institutions. It can be also used by teachers of geographical specialties as it has a significant number of interesting and useful material about physico-geographical features in Ukraine.
Physical Geography of Ukraine
Keywords: практикум; номенклатура; географія